Facilities management in PLKN centre / Nor Diana Aziz - Aziz, Nor Diana (2009)
Program Latihan Khidmat Negara (PLKN) is the module to develop a young generation who are patriotic and with love for their country and install spirit of caring and volunteerism among youth. FM operation was a highlight at all of PLKN centers. The chapters in this study were arranged in six (6) chapters. Introduction, literature review of FM. Management of facilities at PLKN centre, analysis procedure, analysis and finding and was finalize in last chapter of conclusion and recommendation. They were three (3) objectives stated in chapter 1. The source of the study conduted by secondary data and the primary data. The methodology of the study by literature revew, intrument of questionaire to staffs and trainees. From the facilities audit, the facilities at PLKN centre seem low of effectiveness when the unmaintained most facilities during the no participant of training session phase. The facilities at the PLK centre were ineffective during this period. From the summary of trainees and staffs responses, generally, most of them satisfied with the facilities provided by FM operation. This shows that the effectiveness of PLKN centre during the training session phase was effective. However, the level of the effectiveness of the facilities during no participant of training session phase seems was ineffective. The recommendation of the study is stated in the last chapter, from the analysis conducted. Three (7) recommendations are stated in the study; JLKN should outline to set up level of benchmark of each camp to achieve high level of effectiveness for total FM by the facilities provided at the centers. The organization develop tools and technique for generating, evaluating, and synthesizing design solutions based on whole life and minimal environment impact. The facilities provided should be upgraded by most effective current facilities available. The detailed analysis for FM goal of organization should be determined to group the opportunities for facilities goal. The cost-effective would achieve by effective of facilities provided at the PLKN centers. The research necessary for special attention for adaptation to new services and upgrading of the building fabric, services installation and interior fitting which these influence with lack of satisfaction of facilities provided inside of building. The routine maintenance, preventative maintenance should be plan by maintenance schedule to achieve goal of FM. Provide real-time support to occupant such as increase the maintenance crew.